2008
DOI: 10.1007/s10342-008-0234-6
|View full text |Cite
|
Sign up to set email alerts
|

Future orientation and planning in forestry: a comparison of forest managers’ planning horizons in Germany and the Netherlands

Abstract: Long range (or strategic) planning is an important tool for forest management to deal with the complex and unpredictable future. However, it is the ability to make meaningful predictions about the rapidly changing future that is questioned. What appears to be particularly neglected is the question of the length of time horizons and the limits (if any) to these horizons, despite being considered one of the most critical factors in strategic planning. As the future creation of values lies within individual respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Also, our investigation of expiry dates for forestry actions might go beyond planners' perception of time. For example, study of Dutch and German forest managers found that foresters think mainly within a 15-year time horizon (Hoogstra and Schanz 2009). With respect to climate change information, we explored the influence of new information on the decisions of planners about forestry actions.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our investigation of expiry dates for forestry actions might go beyond planners' perception of time. For example, study of Dutch and German forest managers found that foresters think mainly within a 15-year time horizon (Hoogstra and Schanz 2009). With respect to climate change information, we explored the influence of new information on the decisions of planners about forestry actions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore most foresters-like many other professional groups -are concerned about a 10 to 15-year planning horizon (Hoogstra and Schanz 2009). Most of them perceive this period to be realistic because they need to link long forest production periods to production processes and market mechanisms of other important market actors by dividing long-term periods.…”
Section: What Accompanies This Approach?mentioning
confidence: 99%
“…However, ideas about the role of societal perspectives on space and time have also long been part of environmental change research-the Limits to Growth report by Meadows et al (1972) posited that humans have a limited interest in and capacity for action when considering a geographic extent beyond their local communities and over long time periods. Participants in research by Boniecki (1980), Hoogstra andSchanz (2009), andSimons et al (2004) showed a lack of engagement with events on a temporal extent beyond 10-15 years. In contrast to this spatial and temporal "myopia," a "hyperopia" has been found linked to both scales in terms of problem recognition (Gifford et al, 2009;Uzzell, 2000): the longer term future was seen as more problematic than the shorter term by participants in these studies, and global concerns were seen as more problematic than local issues.…”
Section: Perspectives On Scale Dynamics In Socialecological Systems Gmentioning
confidence: 99%